Long-term changes in species and habitat occurrence in the Marine Protected Area of Baia (Gulf of Pozzuoli, Naples) - Gambi, Maria Cristina; Appolloni, Luca; Russo, Giovanni Fulvio; Iacono, Caterina; Miccio, Antonino (Biologia Marina Mediterranea, 2025)
The MPA of Baia (Gulf of Pozzuoli, Naples) is a unique area designed to protect both the natural habitat and the submerged archaeological structures represented by ancient Roman ruins. Long-term changes in benthic species and habitat occurrence in the MPA of Baia are here discussed based on an ecological survey conducted in July 2023 in the frame of the FEAMP project, and designed to check transects and areas where a previous benthic survey was conducted in July 2004. We registered the loss in the whole MPA of the seagrass Cymodocea nodosa and of the two green algae Caulerpa prolifera and C. cylindracea, mixed with Cymodocea, which in 2004 were covering the 36% of the soft bottoms of the area. On the other hand, a Posidonia oceanica bed of ~2 ha extension was recorded between 6 and 7.5 m depth. While a few cryptogenic and alien species were recored, in particular the cryptogenic alga Acetabularia caliculus, recorded at 2-4 m depth in the soft bottoms around Punta Epitaffio, represents the second record of this termophilous species for the Italian coasts.